Safety, Efficacy, and Exposure–Response of Voriconazole in Pediatric Patients With Invasive Aspergillosis, Invasive Candidiasis or Esophageal Candidiasis. Issue 1 (January 2017) - Martin, Judith M.; Macias-Parra, Mercedes; Mudry, Peter; Conte, Umberto; Yan, Jean L.; Liu, Ping; Capparella, M. Rita; Aram, Jalal A.
Abstract : Background: Data on safety and efficacy of voriconazole for invasive aspergillosis (IA) and invasive candidiasis/esophageal candidiasis (IC/EC) in pediatric patients are limited. Methods: Patients aged 2–<18 years with IA and IC/EC were enrolled in 2 prospective open-label, non-comparative studies of voriconazole. Patients followed dosing regimens based on age, weight and indication, with adjustments permitted. Treatment duration was 6–12 weeks for IA patients, ≥14 days after last positive Candida culture for IC patients and ≥7 days after signs/symptoms resolution for EC patients. Primary analysis for both the studies was safety and tolerability of voriconazole. Secondary end points included global response success at week 6 and end of treatment (EOT), all-causality mortality and time to death. Voriconazole exposure–response relationship was explored. Results: Of 53 voriconazole-treated pediatric patients (31 IA; 22 IC/EC), 14 had proven/probable IA, 7 had confirmed IC and 10 had confirmed EC. Treatment-related hepatic and visual adverse events, respectively, were reported in 22.6% and 16.1% of IA patients, and 22.7% and 27.3% of IC/EC patients. All-causality mortality in IA patients was 14.3% at week 6; no deaths were attributed to voriconazole. No deaths were reported for IC/EC patients. Global response success rate was 64.3% (week 6 and EOT) in IA patients and 76.5% (EOT) in IC/EC patients. There was no association between voriconazole exposure and efficacy; however, a slight positive association between voriconazole exposure and hepatic adverse events was established. Conclusions: Safety and efficacy outcomes in pediatric patients with IA and IC/EC were consistent with previous findings in adult patients.